PEMANFAATAN KOLANG-KALING DAN BUAH NAGA MERAH DALAM PEMBUATAN VELVA - Ira Novrika Jalukhu; Vonny Setiaries Johan; Rahmayuni Rahmayuni (SAGU, 2021)
Velva is a frozen dessert made from fruits and vegetables which has low fat and high fiber. The purpose of this research was to obtain the best combination of sugar palm fruit and red dragon fruit puree on the quality of velva. This study used a completely randomized design with five treatments and three replications, resulting in 15 experimental units. The treatments in this research were the ratio of sugar palm fruit puree and red dragon fruit puree, included with level namely 90:10, 80:20, 70:30, 60:40, 50:50. Parameters observed in this study included were overrun, melting time, crude fiber content, total solids, pH, antioxidant and sensory assessment (descriptive and hedonic taste). Results of the research showed that addition of sugar palm fruit puree and red dragon fruit puree significantly affected to overrun, melting time, crude fiber, total solids, pH, antioxidant and sensory taste. The best treatment was a treatment with sugar palm fruit puree and red dragon fruit puree 50:50 with 5.46 % overrun, 7.35 minutes melting time, 1.30 % crude fiber, 23.92% total solids, 3.32 pH, and 80.13 IC50 (μg/ml) antioxidant. The result of the descriptive test of the velva from the best treatment was purple, scented with red dragon fruit flavor, red dragon fruit taste, soft textured, and for overall acceptance the panelists like the velva produced.